Can social adversity and mental, physical and oral multimorbidity form a syndemic? A concept and protocol paper - Easter Joury; Easter Joury; Eliana Nakhleh; Ed Beveridge; Derek Tracy; Derek Tracy; Derek Tracy; Derek Tracy; Ellie Heidari; Ellie Heidari; David Shiers; David Shiers; et al. (Frontiers in Psychiatry)
BackgroundClustering mental, physical and oral conditions reduce drastically the life expectancy. These conditions are precipitated and perpetuated by adverse social, economic, environmental, political and healthcare contextual factors, and sustained through bidirectional interactions forming potentially a ‘syndemic’. No previous study has investigated such potential syndemic. Thus, the present project aimed to (i) test for syndemic interactions between social adversity (socioeconomic adversity and traumatic events) and mental, physical and oral multimorbidity using the syndemic theoretical framework; and (ii) determine whether the syndemic relationships vary by age, sex and ethnicity.MethodsData from three large-scale population-based databases: UK BioBank, US National Health and Nutrition Examination Survey (NHANES) and the Research with East London Adolescents Community Health Survey (RELACHS) will be analysed. Structural equation modelling (SEM) will be utilised to conceptualise syndemic factors and model complex relationships between directly observed and indirectly observed (latent) variables (syndemic constructs).Discussionthe syndemic conceptualisation provides a valuable framework to understand health and illness, and hence to better design and deliver effective and cost-effective preventative and curative integrated (syndemic) care to improve patient and population health. Such syndemic care aims to address the social determinants of health, whilst simultaneously managing all interlocked conditions.